ANALISIS MINAT BELAJAR SISWA TERHADAP PEMBELAJARAN MATEMATIKA PADA SISWA SMA DI KABUPATEN BANDUNG BARAT - Astri Yuliani Nurhafifah; Mayasari Mayasari (Departement of Mathematics Education, 2019)
The purpose of this research is to know student’s learning interest, in mathematics learning of high school students in West Bandung Regency. The method used in this research is survey method. The research technique was carried out by distributing questionnaires, which were then analyzed descriptively. The questionnaire consisted of thirthy questions with four alternative answers, which is